Islamic Education in Forming an Education System: Bibliometric Inquiry - Vika Ayu Rahmadhani; Muhamad Wildan Shohib; Muhamad Subhi Apriantoro; Afief El Ashfahany; Azam Othman (Yayasan Letiges Konsultan Sosial, 2023)
This study aims to reflect on the improvement and course of research on the Islamic religious education system in publications indexed by the Scopus database. This study uses bibliometric analysis techniques to examine all Islamic education and learning publications indexed in the Scopus database from 1972 to 2023. The obtained data were analysed using Microsoft Excel and R/R Studio. Visually analyse keyword occurrence and document citation using VOSviewer. The author found 695 matching publications with specified features, topics, and criteria. The most relevant authors are those whose work is successfully published and indexed by Scopus. The author with the highest influence is indicated by the author with the highest bar, namely Majdzadeh, R., and the author with the least influence is indicated by the author with the lowest bar, such as Chamsine, C., Larijani, B., Lubis, M.A, etc. The limitation of this study is that only data sets or metadata are extracted from Scopus-indexed publications. Other national and international databases were not included in this study. This study provides an overview of the literature available to educational researchers and provides recommendations for future research.